Adaptation and implementation of intercultural activities from life second edition series in an English classroom (2023)
For years, researchers and educators have been saying that teaching English as a Second Language (ESL) requires more than just teaching a set of words and grammar rules or only focusing on the communicative ability. Even more, due to globalization, ESL is somehow aligned with the Intercultural Communicative Competence (ICC). Therefore, this mixed-methods study follows educational design research aimed at piloting supplementary material adapted from Life 4 (Series Second) Edition activities to enhance learner’s ICC in a B1+ course at a binational center in Colombia. The study entailed three main phases: baseline, intervention, and retrospective analysis. In the baseline phase, a focus group, class observations and a survey were conducted. Then, in the intervention phase, 24 supplementary material were designed and 37% were implemented. Finally, in the last retrospective analysis phases, teachers expressed they could not apply those activities due to difficulties with time and priorities. On the other hand, it is possible to assert that teachers focused on the noticing and comparing phase, neglecting the other components of Liddicoat and Scarino's model of language learning.